Education for Sustainable Development Pedagogy in Pre-Primary Social Studies Curriculum in Kenya: Review of Literature - Ganira Khavugwi Lilian (Journal La Edusci, 2022)
Education for sustainable development (ESD) emphasizes integration of values inherent in all curricular to encourage changes in behavior that allows a just society for all. The ESD pedagogy initiated by UNESCO highlights a shift towards active participation and experiential learning methods which engage learners in critical thinking and ability to act responsively for informed citizenship. Integrating sustainable development pedagogies, which include problem-based, inquiry-based and reflective learning in social studies curriculum, encourages creativity, critical thinking and respect for cultural diversity and creation of a sustainable society. Anchored on constructivism theory, the study used data from both primary and secondary sources on influence of ESD through social studies curriculum. Secondary data was sourced mainly from the internet, focusing on the work of UNESCO on education for sustainable development. Literature reviewed established that social studies curriculum, which is entrenched in values of humanity provides opportunities for lifelong learning and sustainable development. The ESD pedagogies facilitate learning of knowledge, promotes skills, perspectives and values that sustainable societies require for spurring the 21st Century and beyond. The systematic review recommends that teaching and learning of social studies should incorporate appropriate pedagogies for sustainable development for learners to progress to adult life as responsible and functional citizens for collective harmony.